2022
DOI: 10.1111/jopy.12713
|View full text |Cite
|
Sign up to set email alerts
|

Self‐esteem development during the transition to work: A 14‐year longitudinal study from adolescence to young adulthood

Abstract: Introduction Previous studies examined the trajectory of self‐esteem during critical developmental periods and over the life‐span. However, little is known about how self‐esteem changes during the school‐to‐work transition. Method We examined the effect of beginning a job for the first time on self‐esteem development, using data from 368 adolescents assessed up to six times across a 14‐year time span. Specifically, we analyzed the pattern of self‐esteem change during the transition to work and whether the self… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 105 publications
3
11
0
Order By: Relevance
“…Since some individuals increased, whereas others decreased, these effects could have canceled each other out. Similar patterns of substantial individual differences in self-esteem change have been found in two previous studies on university-to-work transition (Filosa et al, 2022, Reitz et al, 2020 and one study on transition to (re)employment . Considerable individual differences in self-esteem change during the university-to-work transition reiterate the importance of examining individuals' subjective experiences of the transition to understand why individuals differ in their self-esteem change (Luhmann et al, 2021).…”
Section: Pride and Self-esteem Change Across The Transition From Univ...supporting
confidence: 82%
See 2 more Smart Citations
“…Since some individuals increased, whereas others decreased, these effects could have canceled each other out. Similar patterns of substantial individual differences in self-esteem change have been found in two previous studies on university-to-work transition (Filosa et al, 2022, Reitz et al, 2020 and one study on transition to (re)employment . Considerable individual differences in self-esteem change during the university-to-work transition reiterate the importance of examining individuals' subjective experiences of the transition to understand why individuals differ in their self-esteem change (Luhmann et al, 2021).…”
Section: Pride and Self-esteem Change Across The Transition From Univ...supporting
confidence: 82%
“…Some job beginners increased in their self-esteem, whereas others decreased, which suggested a destabilization of self-esteem during the transition. A recent study found that self-esteem steeply increased before Italian high school and university students' transition to work, and that the increase was slower, more gradual after the transition (Filosa et al, 2022). This study also found that individuals differed in self-esteem change to a greater extent after than before the transition.…”
Section: Self-esteem Development During the University-to-work Transi...supporting
confidence: 62%
See 1 more Smart Citation
“…For example, research suggests that global self-esteem has benefits for many life outcomes (Orth & Robins, 2022), but if global self-esteem influences domain-specific self-esteem, it is possible that changes in domain-specific self-esteem account for (i.e., mediate) some of the positive effects of global self-esteem. Third, if domain-specific self-esteem influences global self-esteem, this knowledge could help to better understand how global self-esteem is influenced by people’s experiences in important life domains, such as social relationships, school, and work (Filosa et al, 2022; Harris & Orth, 2020; Krauss & Orth, 2021; Reitz et al, 2022; Wagner et al, 2018). Thus, it is possible that domain-specific self-esteem mediates some of the effects of life experiences on global self-esteem.…”
Section: Theoretical Perspectives On the Relation Between Global And ...mentioning
confidence: 99%
“…When having found a job, they need to find out what their new role as a member of the workforce is and how to perform well, while they also need to adjust to a new social group of colleagues (Bauer et al, 2007). People differ in how they experience and adjust to this transition, with vast differences in how their self-esteem and life satisfaction changes (Filosa et al, 2022;Haase et al, 2012;Reitz et al, 2020). In the present study, we examined whether a salient personal narrative helps explain these individual differences in self-esteem and life satisfaction.…”
Section: The Transition From Education To Workmentioning
confidence: 99%